Political Attitude and Personality in a Democratic Society - Markovikj, Marijana (Kosovo Public Policy Cente, 2010)
Achieving democracy is the main goal and long term dedication of all Western Balkan countries, especially in the context of the efforts to achieve EU membership. Democratization is a long-term process for these countries, where transition was connected to war (as was the transition of former Yugoslav republics). Transition is a period between two political systems. The transition away from socialism in former Yugoslavia began with nationalism and traditionalism. Thus, the transformation of political attitudes (which means the transformation of political culture) is essential to establishing a democratic society. Establishing democratic institutions in those countries is just a beginning. As researchers and theoreticians have note, democracy cannot be sustained in a society without transforming the political attitudes and political culture of citizens. The political culture of citizens should contain elements of a participative culture such as having a sense of responsibility for society and becoming concerned about human rights and human development. Research conducted in the Republic of Macedonia shows that socialism is still the dominant political ideology among students. Almost 80% of students have socialist political beliefs (Markovic, 2008). Another research study among students shows the internalizing of political attitudes depends on certain personality traits (Markovic, 2009). These findings show that personality can be shaped, and that certain personality profiles correspond with democratic identity. For example, this research (Markovic, 2009) shows that neuroticism influences introjections of traditional attitudes about family, education and freedom of speech. Openness to experiences and extroversion influence attraction to democratic attitudes about family, education, and freedom of speech. These findings show that personality can be shaped through education and most importantly, through real life lessons about good practices of democratic credo.